Inhibition of estrogen sulfation by Xian-Ling-Gu-Bao capsule. Issue 225 (January 2023) - He, Liangliang; Chen, Chanjuan; Duan, Shuyi; Li, Yang; Li, Chuan; Yao, Xinsheng; Gonzalez, Frank J.; Qin, Zifei; Yao, Zhihong
Abstract: Xian-Ling-Gu-Bao capsule (XLGB) is a widely prescribed traditional Chinese medicine used for the treatment of osteoporosis. However, it significantly elevates levels of serum estrogens. Here we aimed to assess the dominant contributors of sulfotransferase (SULT) enzymes to the sulfation of estrogens and identify the effective inhibitors of this pathway in XLGB. First, estrone, 17β-estradiol, and estriol underwent sulfation in human liver S9 extracts. Phenotyping reactions and enzyme kinetics assays revealed that SULT1A1, 1A2, 1A3, 1C4, 1E1, and 2A1 all participated in estrogen sulfation, with SULT1E1 and 1A1 as the most important contributors. The incubation system for these two active enzymes were optimized with Tris-HCl buffer, DL-Dithiothreitol (DTT), MgCl2, adenosine 3'-phosphate 5'-phosphosulfate (PAPS), protein concentration, and incubation time. Then, 29 compounds in XLGB were selected to investigate their inhibitory effects and mechanisms against SULT1E1 and 1A1 through kinetic modelling. Moreover, in silico molecular docking was used to validate the obtained results. And finally, the prenylated flavonoids (isobavachin, neobavaisoflavone, etc.) from Psoralea corylifolia L., prenylated flavanols (icariside II) from Epimedium brevicornu Maxim., tanshinones (dihydrotanshinone, tanshinone II-A, ) from Salvia miltiorrhiza Bge., and others (corylifol A, corylin) were identified as the most potent inhibitors of estrogen sulfation. Taken together, these findings provide insights into the understanding regioselectivity of estrogen sulfation and identify the effective components of XLGB responsible for the promotion of estrogen levels. Graphical Abstract: ga1 Highlights: Sulfation of estrogens by liver S9 fractions and expressed SULT isozymes were fully explored. Regioselectivity of estrogens- O -sulfation by human liver S9 fraction and recombinant SULT enzymes was summarized. Inhibition potential of XLGB-related compounds against SULT1A1 and 1E1 was assessed. Molecular docking prediction was further utilized to validate the inhibition results.